Chronic Lymphocytic Leukemia: A Literature Review - Maulana, Muhammad Rafi; Nurmawaddah, Intan; Ilmiah, Janiya Abdila; Damayanti, Ida Ayu Andara; Wiguna, I Made Danuarta; Anggoro, Joko; Maulana, Akhada (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Chronic Lymphocytic Leukemia (CLL) is a slowly progressing hematological cancer characterized by the accumulation of abnormal B lymphocytes in the blood, bone marrow, and lymphatic tissue, commonly affecting the elderly. This review aims to comprehensively review the epidemiology, molecular basis of the disease, clinical symptoms, diagnosis, and therapeutic advances of CLL, emphasizing the importance of shifting treatment approaches towards more precision therapy. A literature search was conducted through PubMed, Scopus, and Web of Science using the keywords